The Effects of Gold and Oil Prices on Saudi Arabia’s GDP from 2001 to 2023 - Almatar, Alla; Alshammari, Najla; Almohaya, Reema; Alajmi, Nourah; Adbualqader, Aseel; Alsayed, Helah; Alnafisah, Dr. Hind (American Journal of Economics, 2025)
Purpose: The purpose of this study is to examine how fluctuations in oil and gold prices have influenced Saudi Arabia's GDP from 2001 to 2023. Given the country's status as one of the world's largest oil exporters, its economic stability is closely tied to changes in oil prices. While gold plays a less central role, it still impacts the economy by shaping investor confidence and serving as a safe haven during times of uncertainty. Materials and Methods: The study employs a detailed analysis of historical trends and economic indicators to explore the relationship between oil and gold prices and their effects on GDP. A multiple linear regression model is used to examine these relationships. Factors such as inflation and investment patterns are considered to assess the strength and implications of these correlations. Findings: The findings reveal that oil prices have a significant and direct impact on Saudi Arabia's GDP growth, with an increase in oil prices being associated with a substantial decrease of 6.52 units in GDP. This underscores the country's economic reliance on oil exports. On the other hand, gold prices positively contribute to GDP, with an increase of 2.20 units, highlighting their role in influencing economic factors such as inflation, investment trends, and investor sentiment. These results underscore the vulnerabilities associated with commodity price fluctuations and their substantial impact on economic performance. Implications to theory, Policy and Practice: To address these challenges, the study recommends that policymakers focus on stabilizing oil and gold prices to mitigate economic volatility. Additionally, achieving the goals of Vision 2030 is essential, emphasizing the need to diversify the economy and reduce dependence on oil. Strengthening economic resilience and fostering sustainable growth strategies are critical steps toward ensuring long-term prosperity.